Bimbingan Klasikal Dengan Teknik Problem Based Learning Untuk Meningkatkan Berpikir Kritis Siswa SMP Negeri 1 Denpasar - Luk Luk Yata Lalak Muslimin; Sri Muliya Hidayani; I Nyoman Rajeg Mulyawan (Institut Teknologi dan Bisnis (ITB) Semarang, 2024)
The low ability to think critically is influenced by many factors, one of which is the application of counseling guidance which is less varied. This research aims to determine students' critical thinking abilities and how students respond to learning through the application of classical guidance services with Problem Based Learning Techniques to determine the increase in students' critical thinking abilities at SMP Negeri 1 Denpasar. The design of this research uses Pre-Experimental Design with a One Group Pre-Test Post-Test Design research design. The population in this study were all students in class VIII of SMP Negeri 1 Denpasar consisting of 4 classes, while the sample in the research was class VIII B. The results of data analysis showed that students' critical thinking skills were provided with classical guidance services with Problem Based Learning techniques on the theme of communication ethics with Class VIII B peers at SMP Negeri 1 Denpasar experienced an increase with a pre-test score of 16.85 and a post-test score of 77.40. The t-test results show tcount = 22.76, with d.b 26 obtained ttable = 1.70. These results show tcount>ttable, so Ho is rejected and it can be concluded that there is an increase in students' critical thinking abilities in classical guidance services on the theme of communication ethics with class VIII peers using the Problem Based Learning technique (Ha is accepted). And student learning responses with an average score of 84 are included in the very good category.